Legal Counseling on The Mechanism for Handling Women in Conflict with The Law - Aswandi, Aswandi; Supriadi, Moh; Yuliana, Yuliana; Natalia, Kristiani (AIWADTHU: Jurnal Pengabdian Hukum, 2025)
Introduction: Over Capacity: Correctional institutions continue to be a deeply rooted issue in Indonesia's criminal justice system. This poses a challenge for officers in fulfilling basic rights, especially for vulnerable groups such as women. In addition, the mechanisms for handling women who come into conflict with the law remain susceptible to gender injustice, particularly in terms of fulfilling basic rights such as rehabilitation, facilities and infrastructure, as well as access to what is entitled to inmates.Purposes of The Devotion: This legal counseling aims to increase understanding regarding the mechanisms for handling women in conflict with the law at the Class II A Pontianak Women's Correctional Institution.Method of The Devotion: Legal counseling activities are conducted using a lecture method to deliver material, followed by a question-and-answer session between inmates and the presenter. Observations are conducted for evaluation and monitoring after the counseling session.Results Main Findings of the Devotion: The results of this study indicate that the mechanism for handling Women in Conflict with the Law in relation to legal aid is still not optimal due to the lack of socialization and limited access to obtain it. Therefore, this study is expected to contribute as an effort to increase the understanding of officers and inmates about the handling mechanism related to legal aid for inmates by offering access to legal aid through the Legal Aid Institute at the Faculty of Law, Tanjungpura University.